THE INFLUENCE OF SERVICE QUALITY ON CONSUMER SATISFACTION OF HONDA MOTORCYCLES IN PT. DAYA ANUGRAH MANDIRI PAREPARE - Ulfa Natsir; Anastasia D'Ornay (Asosiasi Dosen Muda Indonesia, 2022)
This study conducted with destination namely (1) For knowing quality service take effect by Partial to satisfaction Honda motorcycle consumers at PT. Daya Anugrah Mandiri Parepare. (2) For knowing service take effect by simultaneous to satisfaction Honda motorcycle consumers at PT. Daya Anugrah Mandiri Parepare. Research results show that (1) Physical evidence (X1) The test results show the value of t = (-0.221) with score significance of 0.826 > 0.05. (2). Reliability (X2) The test results show the value of t = (-0.530) with a significance value of 0.598 > 0.05. (3). Responsiveness (X3) The test results show the value of t = 5.974 with score significance of 0.000 > 0.05. (4). Guarantee (X4) The test results show the value of t = 0.223 with a significance value of 0.824 > 0.05. (5). Empathy (X5) The test results show the value of t = 0.675 with a significance value of 0.502 > 0.05. (6). physical evidence, reliability, responsiveness, assurance and empathy have a positive and significant effect (0.000 <0.05) simultaneously on consumer satisfaction. The results of the analysis of the value of R Square (R2) is 0.594 or of 59.4% while the remaining 41.6% is explained by other factors that do not entered in the research model this.